Who Is Confronting Whom? Conflicts About Renewable Energy Installations in Germany - Fuchs, Gerhard (Journal of Leadership, Accountability and Ethics, 2021)
The electricity transition in Germany has always been a contentious issue. Since the end of the second decade of the new millennium, the impression arises that the main debate is between interests of society on the one hand and local or regional opposition on the other hand. Even research organizations for some years spent a lot of effort studying the question, whether the electricity transition lacks acceptance in the population, at least in areas in which new installations (especially) wind and power grids are being built. As such, protest activities have become an eminent political as well as practical problem. The present article analyzes four selected siting conflicts in order to show that these conflicts are not one-dimensional. A variety of actors from different fields are participating, with different aims and using different framing strategies. Both theoretically as well as empirically, it seems difficult to locate interests of the society as opposed to interests of local or regional communities. Both local as well as societal interests are not uniform and stable. Conflicts should be treated as situated in a four-dimensional space in which social, topical, temporal and spatial aspects intermingle.